MENUMBUHKAN KEMAMPUAN MEMBACA AL-QUR’AN DENGAN METODE AL-BAGHDADI PADA SISWA/I KELAS 1 MADRASAH IBTIDAIYYAH - Ai Umir Fadhilah (al-Iltizam: Jurnal Pendidikan Agama Islam, 2024)
The ability to read the Koran is currently still relatively low, especially in Madrasah Ibtidaiyyah students who still cannot read the Koran properly. In fact, many do not even know hijaiyyah letters. The ability to read the Koran needs to be taught to students through a learning process, this is to maintain reading the Koran. The purpose of this study was to find out how to foster the ability to read the Qur'an in grade 1 Madrasah Ibtidaiyyah and the obstacles in its implementation. This research with a qualitative approach uses a case study conducted at MI Ma'arif Bego DI Yogyakarta. Participants in this study involved 1 person, namely the tahfidz teacher at the Ibtidaiyyah Madrasah. The results of the study show that the process of implementing learning to read the Koran using the al-Baghdadi method is that students can easily read the Koran quickly and accurately, and there are guidebooks and rhymes to make it easier for students to memorize. hijaiyyah letters and the laws of reading the Koran. Thus learning the Koran for grade 1 students of Madrasah Ibtidaiyyah is suggested to be more appropriate using the al-Baghdadi method.